Anxiety Analysis of Petanque Athletes from West Java - Iskandar, Tatang (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The purpose of this study was to analyze the levels of anxiety of West Java pétanque athletes before, during, and after the Provincial Sports Week (PORPROV) XIV match in Ciamis Regency. This study used a quantitative descriptive research design. The population in this study were 146 Petanque athletes who participated in the West Java PORPROV XIV Year 2022 in Ciamis regency. This study used a purposive sample technique with the criteria of medal winners at the West Java PORPROV in 2022. The number of samples obtained was 78 athletes. Theis study used a closed questionnaire as a research instrument. The results of this study show that female athletes of West Java have a relatively high level of anxiety while male athletes have a relatively medium level of anxiety. In general, the participants have medium level of anxiety before and after the match. On the other hand, the participants were shown to have a high level of anxiety during the match.